Contemporary tourism an international approach - Cooper, Chris 1952-; Hall, Colin Michael 1961- (Goodfellow Publishers Limited, 2019)
"The study of tourism and indeed the tourism industry is changing constantly. Now in its fourth edition, Contemporary Tourism: an international approach presents a new and refreshing approach to the study of tourism, considering issues such as overtourism, advances in AI and its impacts, waste management and environmental crisis, the sharing economy and Airbnb, the tourist experience and product development. In particular, it highlights the ongoing threats and opportunities faced by the tourism industry today, and discusses the related management strategies, illustrating the potential implications for the patterns and flow of tourism in the future. Divided into five sections, each chapter has a thorough learning structure including chapter objectives, examples, discussion points, self-review questions, checklists and case studies. URL links are heavily present throughout the text so that users of both hard and electronic formats can have direct links to up to date, authoritative and annotated sources of information. Cases are both thematic and destination-based and always international. They are used to emphasise the relationship between general principles and the practice of tourism looking at areas such as business and special interest tourism and the role of technology. The five sections cover: Contemporary Tourism Systems; The Contemporary Tourist; The Contemporary Tourist Destination; The Contemporary Tourism Industry; and Tourism Futures. " --Publisher.